The risks associated with the use of social media by Generation Z - Răduț, Florin; Sicrea, Cosmin; Andrioni, Felicia (Technium Education and Humanities, 2023)
The development of social media has had a significant impact on society and Generation Z has been directly affected by the new modern means of communication. In addition to the positive implications, there are a wide range of risks to which users are exposed on the Internet. Direct social interactions, physical activities, time spent with friends in nature are alternatives to limit the time spent online. Through informative campaigns, appropriate laws and collaboration between educational agents young people can develop the skills they need to cope with risky situations. Thus, the positive effects of the online environment should be maximized to contribute to personal development. The methodology of the research was characterized by the method of focus groups, and the group that was studied was made up of 13 young people. The main results highlight the existing risks for the active users of social networks, such as: addiction, narcissism, destruction of interpersonal relationships, exposure to immorality, etc.